2011
DOI: 10.1093/brain/awr217
|View full text |Cite
|
Sign up to set email alerts
|

A 12-year follow-up in sporadic inclusion body myositis: an end stage with major disabilities

Abstract: Sporadic inclusion body myositis is considered to be a slowly progressive myopathy. Long-term follow-up data are, however, not yet available. Follow-up data are important with a view to informing patients about their prognosis and selecting appropriate outcome measures for clinical trials. We performed a follow-up study of 64 patients with sporadic inclusion body myositis who participated in a national epidemiological study in the Netherlands. Case histories were recorded, and manual and quantitative muscle te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
192
3
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 172 publications
(209 citation statements)
references
References 26 publications
12
192
3
2
Order By: Relevance
“…In the Dutch study, aspiration pneumonia and cachexia were the most frequent causes of death, while cancer was found to be less common than in the general population (Benveniste et al, 2011, Cox et al, 2011.…”
Section: Natural Historymentioning
confidence: 92%
See 2 more Smart Citations
“…In the Dutch study, aspiration pneumonia and cachexia were the most frequent causes of death, while cancer was found to be less common than in the general population (Benveniste et al, 2011, Cox et al, 2011.…”
Section: Natural Historymentioning
confidence: 92%
“…A Dutch study of 61 patients who were re-examined after a mean of 12 years estimated an annual rate of decline in muscle strength of 3.5% based on manual muscle testing (MMT) and 5.4% with quantitative muscle testing (QMT) (Cox et al, 2011). A more rapid rate of deterioration (9.5% per annum) was found in a Swedish study of 66 patients assessed with hand-held myometry over a mean follow-up period of 5 years (Lindberg and Oldfors 2012).…”
Section: Natural Historymentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical presentation is heterogenous and at times difficult to distinguish from other inflammatory myopathies (muscle weakness and atrophy), motor‐neuron disease (asymmetry), and muscular dystrophies (slowly progressive disease) 3. In two large observational studies, the mean age of onset has been reported to be 59 ± 9 and 61 years, respectively 9, 11. The cardinal symptom of this highly debilitating disease is the late‐onset steady acquisition of muscular weakness and atrophy over a long period of time whilst sensory function is completely preserved.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…The cardinal symptom of this highly debilitating disease is the late‐onset steady acquisition of muscular weakness and atrophy over a long period of time whilst sensory function is completely preserved. The decline of muscle strength ranges between 3.5 and 5.5% per annum 9, 11. Unlike other myopathies, during which proximal muscles are initially affected, IBM shows early involvement of distal muscles.…”
Section: Clinical Presentationmentioning
confidence: 99%